2023
DOI: 10.1111/csp2.12932
|View full text |Cite
|
Sign up to set email alerts
|

Extinction risk patterns in a biodiversity hotspot—The case of Thesium (Santalaceae) in the Greater Cape Floristic Region

Abstract: Ecologically specialized plants are expected to be at greater risk of extinction than generalists due to climate change. Such risk is greatest in biodiversity hotspots such as the Greater Cape Floristic Region (GCFR), which accommodates both ecological specialists and generalists. Thesium L., a genus with the highest number of species in Santalaceae and the most diverse in Africa, offers an appropriate system for evaluating both the correlates of range extent and specialization and the relative extinction risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
1
1
0
Order By: Relevance
“…Many Thesium species in low-latitude regions are facing a reduction in suitable habitats compared to other plant species within the genus. The results of the distribution models of Thesium species from the Cape Floristic Region indicate that over 50% of the species show a reduction trend, supported by our results 67 . Unfortunately, there are fewer distribution modeling studies on the complete ecological niche of Thesium species.…”
Section: Discussionsupporting
confidence: 87%
“…Many Thesium species in low-latitude regions are facing a reduction in suitable habitats compared to other plant species within the genus. The results of the distribution models of Thesium species from the Cape Floristic Region indicate that over 50% of the species show a reduction trend, supported by our results 67 . Unfortunately, there are fewer distribution modeling studies on the complete ecological niche of Thesium species.…”
Section: Discussionsupporting
confidence: 87%
“…The likely impact, for example on high mountain versus lowland species of Erica , is still largely unclear. Analysing the genus Thesium in the CFR , Zhigila et al (2023) used niche modelling to project past, current and future distributions and tested for phylogenetic signal in range size, niche specialisation and threat status. They concluded that species at greatest risk were not more closely related than might be expected by chance and that the range of some species would decrease whilst others increased under projected climatic conditions.…”
Section: Discussionmentioning
confidence: 99%